α‐lipoic acid reduces fatty acid esterification and lipogenesis in adipocytes from overweight/obese subjects - Fernández‐Galilea, Marta; Pérez‐Matute, Patricia; Prieto‐Hontoria, Pedro L.; Sáinz, Neira; López‐Yoldi, Miguel; Houssier, Marianne; Martínez, J. Alfredo; Langin, Dominique; Moreno‐Aliaga, María J. (Obesity (Silver Spring, Md.), 2014)
Objective α‐Lipoic acid (α‐LA) is a natural occurring antioxidant with beneficial effects on obesity. The aim of this study was to investigate the putative effects of α‐LA on triglyceride accumulation and lipogenesis in subcutaneous adipocytes from overweight/obese subjects and to determine the potential mechanisms involved. Methods Fully differentiated human subcutaneous adipocytes were treated with α‐LA (100 and 250 µM) during 24 h for studying triglyceride content, de novo lipogenesis, and levels of key lipogenic enzymes. The involvement of AMP‐activated protein kinase (AMPK) activation was also evaluated. Results α‐LA down‐regulated triglyceride content by inhibiting fatty acid esterification and de novo lipogenesis. These effects were mediated by reduction in fatty acid synthase (FAS), stearoyl‐coenzyme A desaturase 1, and diacylglycerol O‐acyltransferase 1 protein levels. Interestingly, α‐LA increased AMPK and acetyl CoA carboxylase phosphorylation, while the presence of the AMPK inhibitor Compound C reversed the inhibition observed on FAS protein levels. Conclusions α‐LA down‐regulates key lipogenic enzymes, inhibiting lipogenesis and reducing triglyceride accumulation through the activation of AMPK signaling pathway in human subcutaneous adipocytes from overweight/obese subjects.